Social Taboo And New Worlds: Resilience of Identity Facing Ecological and Cultural Crisis - Hansen, Andreas T. (SCARAB, 2022)
Environmental media and literature have become increasingly fascinated with the future changes society and mainstream culture might face. As the world faces anthropogenic climate change and ecological disaster, the existential systems of Indigenous peoples provide examples of modern adaptation and change, through remaining true to cultural valuing and their systems of ecological management. The practices surrounding taboo provide frameworks for establishing environmental considerations and societal worldviews. Through the analysis of the case studies of the Pueblo, Inuit, and Tagbanuwa, a social relationship with nature can be identified, which when broken turns into cultural and ecological consequences. These cultural structures and norms, in turn, generate methods of repair and punishment, with cultural healing occurring through acts such as banishment or ceremonies. The breaking of ecological and cultural frameworks due to climate stress or cultural assimilation results in narratives shifting towards explaining consequences resulting in environmental disaster through the lens of apocalypse and revitalization. The hope of survival and the cultural systems that promote Indigenous resilience generate the idea of new identities for the impacted communities, as their emerging culture forms around adaptation and the reimagined world left to them. With these frameworks in mind, modern environmental ethics concerning climate change might be formed from the incorporation of Indigenous media for those directly affected by these pressures, as social tools taking an early step towards the future with current actions of adaptation and resilience.